solve for x X^2 – 12 = - 4x

Question

Asked 4/24/2012 11:04:39 PM

Updated 8/5/2015 1:40:31 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [8/5/2015 1:40:25 AM]

s

Rating

8

x^2 – 12 = - 4x;

x^2 + 4x - 12 = 0;

(x + 6)(x - 2) = 0;

x + 6 = 0; x = -6;

x - 2 = 0; x = 2

x = {-6, 2}

x^2 + 4x - 12 = 0;

(x + 6)(x - 2) = 0;

x + 6 = 0; x = -6;

x - 2 = 0; x = 2

x = {-6, 2}

Added 8/5/2015 1:40:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [8/5/2015 1:56:06 AM]

using PEMDAS 2 + 4 x 6^2 – 8 **Weegy:** 6 x 3 + 10 ? 2 = 18+5 = 23 (More)

Question

Updated 4/24/2012 8:12:11 AM

1 Answer/Comment

2 + 4 x 6^2 – 8

= 2 + 4 * 36 - 8

= 2 + 144 - 8

= 138

= 2 + 4 * 36 - 8

= 2 + 144 - 8

= 138

Added 4/24/2012 8:12:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/31/2014 5:14:28 PM]

9. Evaluate: x^2 – 5x 3 for x = -5 **Weegy:** x2 ? 5x + 3 for x = -5= (-5)^2 ? 5(-5) + 3 =((-5)^2) - (5 * (-5)) + 3 = 53 **User:** 10. Write as a mathematical expression using parentheses and brackets. Then evaluate:
Subtract 3 from 15. Divide this difference by 2. Multiply this quotient by 4.
**Weegy:** [(15 - 3)/2] 4 **User:** Simplify: 5(3x + 7) **Weegy:** (3x-2) squared is 9x^2 - 12x + 4. (More)

Question

Updated 6/30/2014 8:21:31 AM

1 Answer/Comment

5(3x + 7)

=(5)(3x)+(5)(7)

15x+35

=(5)(3x)+(5)(7)

15x+35

Added 6/30/2014 8:21:30 AM

This answer has been confirmed as correct and helpful.

5. Simplify: 5(3x + 7) **Weegy:** 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! (More)

Question

Updated 6/5/2014 6:25:54 PM

1 Answer/Comment

5(3x + 7) = 15x + 35

Added 6/5/2014 6:25:52 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/6/2014 12:09:30 PM]

factor 16x^2 – 9 **Weegy:** 16x^(2)-12x-10
Factor out the GCF of 2 from each term in the polynomial.
2(8x^(2))+2(-6x)+2(-5)
Factor out the GCF of 2 from 16x^(2)-12x-10.
2(8x^(2)-6x-5)
Find the factors such that the product of the factors is the trinomial 8x^(2)-6x-5. [ This can be done by trial and error and checked using the FOIL method of simplifying polynomials.
2(2x+1)(4x-5) ] (More)

Question

Updated 6/28/2014 3:00:28 PM

1 Answer/Comment

Answer: (4x-3)(4x+3)

Added 4/24/2012 9:22:32 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/28/2014 3:00:28 PM]

(4÷ 2) + 8( 5-3)^2 **Weegy:** (4 ? 2) + (8 * (5 - 3) * 2) = 34 **User:** -8 – 72 ÷ 9 x 4^2 + 11 **Weegy:** -333 is the answer to -8 ? 72 ? 9 x 42 + 11 using PEMDAS (More)

Question

Updated 4/24/2012 8:17:10 AM

2 Answers/Comments

-8 – 72 ÷ 9 x 4^2 + 11

= -8 – 72 ÷ 9 x 16 + 11

= -8 - 8 x 16 + 11

= -8 - 128 + 11

= -125

= -8 – 72 ÷ 9 x 16 + 11

= -8 - 8 x 16 + 11

= -8 - 128 + 11

= -125

Added 4/24/2012 8:17:10 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/12/2014 12:17:21 PM]

34,009,970

questions answered

There are no comments.